A highly transparent and photothermal composite coating for effective anti-/de-icing of glass surfaces. Issue 13 (6th June 2022) - Guo, Wei; Liu, Cui; Li, Nian; Xi, Min; Che, Yamin; Jiang, Changlong; Zhang, Shudong; Wang, Zhenyang
Abstract : A direct spraying method on a glass surface to obtain Cu7 S4 /silicone sol coatings with high transparency, good photothermal conversion, effective anti-/de-icing behavior, and excellent chemical/physical stability. Abstract : Anti-/de-icing of glass surfaces is of great importance in present daily life. The long-standing challenge in this field is largely due to the lack of stable multifunctional coatings that can be conveniently and economically constructed on the glass surface, and more importantly, are capable of retaining the original transparency of glass ranging from the visible to the near infrared spectrum. Herein, a direct spraying sol method on the glass surface to prepare a highly transparent and photothermal composite coating is reported. Such multifunctional coating of Cu7 S4 nanoparticles/organo-silicone sols has displayed a good photothermal conversion property and hydrophobic property and therefore yields excellent anti-icing and self-melting ice properties. The condensation time of water droplets can be extended to 86 s even at −10 °C, which is 3.42 times delayed relative to ordinary blank glass. And the adhesion strength of ice is largely reduced to 72 KPa, which is as low as ∼1/3 that of ordinary glass. Meanwhile, the subcooling of adhering droplets is reduced to −12 °C under one solar illumination condition and exhibits a rapid de-icing capability. More impressively, the prepared functional coating glass shows an outstanding transmittance of more than 75% in the visible region, while it is over the minimum glass transmittance limit allowed by Safety Standards for Glass (GB9656-2016, China). In addition, the multifunctional photothermal glass coating exhibits good physical/chemical stability, which facilitates the long-term application of the coating in different environments.